Poor Families In Banda Aceh and Pidie - Daud Bahransyaf (Jurnal Penelitian Kesejahteraan Sosial, 2017)
Based on the research conducted randomly to 600 heads of poor category families in five sub-districts (that of Syiah Kuala, Banda Raya, Lueng Bata, Ulle Kareng and Baiturrahman Sub-District) of Banda Aceh City, and also by identifying 599 people representing poor families in five sub-districts (that of Glumpang Tiga, Mutiara, Tiro/Truseb, Tangse and Muara Tiga Sub-District) of Pidie District, it was known that there were some socio-economic fundamental changes in their income and expenditure as well as ownership of the goods. Their income and expenditure of households level in both locations concerned had already achieved more than Rp.600.000,- per month. Goods which was previously used to be a secondary need and owned only by middle and upper class society, it had turned out to be primary need for life and their livelihood.Most people possessed mobile phones and motorcycles. Majority of respondents had each a TV of over 14â€ size and a refrigerator. Electricity for lighting had been utilized by most of the poor families in both two research sites. Electricityprogram had reached and been enjoyed by citizens in Banda Aceh City and by that of Pidie District. These empirical facts need to be observed and studied as an input to make adjustment on the aspects or criteria of families in poverty, either done by the related bodies or institutions, or by the authorities concerned in making Government Regulations or Local Government Regulations and Minister Regulations.